A Comparative Analysis of Drivers of Collaborative Governance in Front-of-Pack Food Labelling Policy Processes. Issue 4 (8th August 2018) - Wood, Amanda; Tenbensel, Tim
Abstract: Collaborative governance is one tool for steering decision-making in issues with competing coalitions of actors. Where collaborative governance arrangements are emergent, there is potential for policy actors to develop a bespoke design. To understand what drives effective collaborative governance in these situations, this research applies a comparative framework drawing on the Advocacy Coalition Framework and Multi-Level Governance framework to analyse three collaborative policy development processes for front-of-pack food labelling in Australia, New Zealand and the United Kingdom. Policy actors can use insights from this comparison to inform the development of similar collaborative processes with scope for a bespoke design.